Thiophene-linked tetramethylbodipy-labeled nucleotide for viscosity-sensitive oligonucleotide probes of hybridization and protein-DNA interactions - Güixens-Gallardo, Pedro; Humpolickova, Jana; Miclea, Sebastian Paul; Pohl, Radek; Kraus, Tomáš; Jurkiewicz, Piotr; Hof, Martin; Hocek, Michal (Organic & biomolecular chemistry, 2020)
Cytosine 2'-deoxyribonucleoside dCTBdp and its triphosphate (dCTBdpTP) bearing tetramethylated thiophene-bodipy fluorophore attached at position 5 were designed and synthesized. The green fluorescent nucleoside dCTBdp showed a perfect dependence of fluorescence lifetime on the viscosity. The modified triphosphate dCTBdpTP was substrate to several DNA polymerases and was used for in vitro enzymatic synthesis of labeled oligonucleotides (ONs) or DNA by primer extension. The labeled single-stranded ONs showed a significant decrease in mean fluorescence lifetime when hybridized to the complementary strand of DNA or RNA and were also sensitive to mismatches. The labeled dsDNA sensed protein binding (p53), which resulted in the increase of its fluorescence lifetime. The triphosphate dCTBdpTP was transported to live cells where its interactions could be detected by FLIM but it did not show incorporation to genomic DNA in cellulo.
Keywords: nukleotidy; Protein Binding; Temperature; sekvence nukleotidů; oligonukleotidové sondy; fluorescenční spektrometrie; thiofeny; Cell Line, Tumor; viskozita; Solvents; rozpouštědla; Nucleic Acid Hybridization; DNA vazebné proteiny; kationty; hybridizace nukleových kyselin; DNA-Directed DNA Polymerase; Cations; vazba proteinů; Oligonucleotide Probes; lipidy; Nucleotides; Viscosity; lidé; DNA-dependentní DNA-polymerasy; Humans; DNA; Thiophenes; Lipids; Base Sequence; Spectrometry, Fluorescence; teplota; sloučeniny boru; nádorové buněčné linie; Boron Compounds; DNA-Binding Proteins